Adult Spinal Deformity Correction with Multi-level Anterior Column Releases: Description of a New Surgical Technique and Literature Review. Issue 4 (May 2016) - Demirkiran, Gokhan; Theologis, Alexander A.; Pekmezci, Murat; Ames, Christopher; Deviren, Vedat
Abstract : Study Design: Case series. Objective: To evaluate radiographic and clinical outcomes of adults with spinal deformity treated with multilevel anterior column releases (ACR). Summary of Background Data: Pedicle subtraction osteotomy can be used effectively to correct spinal deformity; however, it is not without complications. ACR is an attractive alternative minimally invasive technique for spinal deformity correction, although few clinical reports on its clinical effectiveness exist. Methods: Adults with spinal deformity who underwent multilevel ACRs (≥2) followed by open posterior instrumentation with a minimum 1-year follow-up were retrospectively reviewed. Deformity radiographic data and clinical outcomes, including the Oswestry Disability Index (ODI) and the EuroQol-5D were analyzed. Results: Eight patients [7 female, 1 male; mean age 65 y (49–79 y)] met inclusion criteria. The mean follow-up was 18.4 months (12–28 mo). The average number of levels treated with an ACR per patient was 2.4 (2–3). There were no anterior approach–related complications. The average number of levels instrumented posteriorly was 8.1 (3–15). Six patients underwent Schwab type 1 posterior osteotomies (partial facetectomies). After the first anterior stage, there was a significant increase in the lumbar lordosis and significant decreases in the sagittal vertical axis, pelvic tilt, and lumbopelvic mismatch ( P <0.05). After the second stage there was no significant change in the sagittal vertical axis, lumbar lordosis, pelvic tilt, or lumbopelvic mismatch relative to the values obtained after ACR. There was significantly less disability postoperatively [ODI: 15 (0–30)] compared with preoperatively [ODI: 46 (16–80)] ( P <0.01). There was significant improvement in general health after operation, as assessed by the EuroQol-5D utility scores [preop: 0.44 (0.21–0.82) vs. postop: 0.71 (0.60–0.80)] ( P =0.01). Back and leg visual analog scale pain scores improved significantly postoperatively. Conclusions: A staged approach using multilevel ACRs with open posterior instrumentation has an acceptable complication profile and provides excellent restoration of sagittal and coronal balance and pelvic parameters in adults with spinal deformity. Abstract : Supplemental Digital Content is available in the text.